Bose-Einstein condensation in an electro-pneumatically transformed quadrupole-Ioffe magnetic trap - Sunil Kumar; Sumit Sarkar; Gunjan Verma; Chetan Vishwakarma; Md Noaman; Umakant Rapol (New Journal of Physics, 2015)
We report a novel approach for preparing a Bose–Einstein condensate (BEC) of ^87 Rb atoms using an electro-pneumatically driven transfer of atoms into a quadrupole-Ioffe magnetic trap (QUIC trap). More than 5 × ${{10}^{8}}$ atoms from a magneto-optical trap are loaded into a spherical quadrupole trap and then transferred into an Ioffe trap by moving the Ioffe coil towards the center of the quadrupole coil thereby changing the distance between the quadrupole trap center and the Ioffe coil. The transfer efficiency is more than 80%. This approach is different from the conventional approach of loading the atoms into a QUIC trap wherein the spherical quadrupole trap is transformed into a QUIC trap by changing the currents in the quadrupole and the Ioffe coils. The phase space density is then increased by forced rf evaporative cooling to achieve Bose–Einstein condensation of more than 10 ^5 atoms.